From Orientalist Sexual Object to Burkini Terrorist Threat: Muslim Women through Evolving Lens. Issue 1 (1st October 2017) - Sana Tayyen
Abstract : Muslim women in Western societies have found themselves caught in a discourse that politicizes them or depicts them through twisted narratives. Crafters of these narratives utilize media, literature, political rhetoric and government policies, to portray Muslim women through lenses that aim to define who they are, not by their own definitions as Muslim women but by the definitions of those who intend to shape society for political or social gains. These lenses have evolved through time, particularly since in the context of historical events and societal realities such lenses cannot seemingly be true for all Muslim women, at all times. Hence, with new images and information that shape our realities, the lenses by which Muslim women have been defined have also shifted and evolved with the changing of historical events. In this article, I outline four historical lenses: (1) lens of sexual objectivity; (2) lens of backwardness and ignorance; (3) lens of domination and subjugation; and the most current lens which we can analyze today in the here and now, (4) the lens of fear and threat. This final lens entails unwarranted associations made between the evil of ISIS terrorism and the innocent play of Muslim women on French beaches. This lens feeds into the greater attitude of Islamophobia. The fear which is broadcast through the media is a fear against a Muslim encroachment that subverts Western values and ways of living. Muslim women voices are silent in these perceptions. Hence, the dominating voice comes from those who hold power through media, government, or education. They are the ones choosing and crafting the narratives and perspectives, defining Muslim women, and Muslims in general, as a threat to Western Democracy and Liberalism.